Employees’ Attitude and Their Performance: A Study of Senior Staff University of Cape Coast (International Journal of Scientific Research and Management (IJSRM), 2021)
How employees feel and behave in an organisation is very important in determining how they will perform any assigned task. As such, employee attitude has been at the centre stage of human resource management strategies as a means to improving their performance and commitment to their job and by extension the performance of the organisation. In this regard, this study examined the causality between the attitude and job performance of senior staff of University of Cape Coast. Due to the large number of staff and demands of the research objectives, a quantitative approach was adopted using a descriptive research design. A sample size of 308 was derived from a population of 1,532 using Krejcie and Morgan (1970). Questionnaire was used to randomly collect data from 308 senior staff. SPSS was used to code and capture the data besides performing factors analysis on the challenges that impede management’s ability to improve the attitude of senior staff. Smart PLS 3 was used to perform partial least square regression analysis on the link between attitude and performance of the staff. The results show that about 43% of changes in senior staff’s job performance can be attributed to changes in their attitude. Also, the attitude of the senior staff can predict about 26% of how they will perform their job. Stimulating innovations and change, improving ethical behaviour and total quality management are the main challenges that impedes management’s ability to improve the attitude of the senior staff in relation to their job performance. For policy implications management should also dedicate resources to mitigating jealousy among staff.